Knowledge and Practice on Water Quality Management and Water-Borne Diseases in Kathmandu, Nepal - Tamrakar, Pratima (Academia Research Journal, 2024)
The present study evaluated the knowledge and practices of people related to water quality and water borne disease in different area of Kathmandu district. Simple random method was used to select households for interview based on structured questionnaire. Further detail data obtained from observation, checklist and pilot survey in water suppliers including Kathmandu Upatyaka Khanepani Limited. Altogether 153 (91 female & 62 female) people in 153 household and 25 water suppliers including KUKL, community water suppliers and private water suppliers were interviewed and ten focus groups discussion were organized with water manager. Collected data were analyzed using MS-Excel 2011. From the analysis, almost of the respondent (91%) replied for their dependency upon water suppliers for water quality and only few (9%) respondents applied laboratory tests for their water quality. The most common source of information for water quality management was television followed by peer group communication and least considered source of information was NGOs and CBOs. Similarly, mostly used treatment practice for water quality improvement was filtration followed by boiling and least used method was treatment plant. Altogether four categorical responses known for water borne disease where rare number of respondents were actively following prevention to be safe from water borne diseases. Knowledge and practice on water quality, and water-borne diseases, among respondent of study area were unsatisfactory. So, the awareness programs regarding water purification, water pollution, storage, and water borne diseases should be carried on a regular basis. The responsible authority should make laws against the water pollution, water storage and distribution that minimize the future consequences of water borne disease.